Comments on the issue of administrative control over the sale of alcoholic beverages via the Internet with reference to the judgment of the Supreme Administrative Court of September 8, 2022, II GSK 2034/18 - Kucharski, Krzysztof (Studia Iuridica Toruniensia, 2024)
The subject of analysis in this article is the question of permissibility limits for retail sales of alcoholic beverages via the Internet in light of the regulatory model of distribution of alcoholic beverages under Polish law. The scope of conducting business in this area has long been a major issue of disputes between entrepreneurs and public administration bodies. This is because the regulation of the Act on Upbringing in Sobriety and Counteracting Alcoholism leaves in this regard a number of doubts regarding the permissible model of providing this type of service. In turn, the needs of business practice are so substantial that it yields a number of solutions in this area, which, however, are questioned by public administration bodies and part of the judicature of administrative courts. One of the recent rulings of the Supreme Administrative Court, dated September 8, 2022, is an example of the resolution of the dispute on the subject.